Automatic Generation of Links in Patent Documents - Souza, C. M.; Santos, M. E.; Meireles, M. R. G. (Anais do Symposium on Knowledge Discovery, Mining and Learning (KDMiLe), 2018)
Patents are organized into classification systems, which assist offices and users in the process of seeking and retrieving such documents. A wide variety of users use the patent systems and the information contained in these documents. In addition to office professionals, such as examiners and analysts, who determine whether the invention satifies the conditions required to be patented and summarize the content of the document, other users such as inventors, researchers, investors and business managers have a keen interest in understanding the content of patents.However, patents are complex legal documents with a significant number of technical and descriptive details, which makes it difficult to identify and analyze the information contained in these documents. An automatic link system associated with some of the terms found in the patents would provide quick access to the concepts contained in specific knowledge bases. This work presents partial results of a project whose objective is the automatic generation of links in patent documents. The experiments were conducted with four subgroups of the United States Patent and Trademark Office (USPTO), which uses the Cooperative Patent Classification (CPC) classification system. In a first step, since documents do not have keywords, meaningful terms were selected to be designated as link origins, using the algorithm X 2 .Once the link destinies were selected, in a later step, keywords with more than one meaning were disambiguated. It is expected, with the creation of automated links, to aid in the reading of patent texts, thus making it easier to access concepts related to the terms presented by the documents and to the understanding of the information disclosed by the inventors.